Efektivitas Konseling Behavioral Teknik Self Management untuk Menurunkan Prokrastinasi Akademik dengan Kovariabel Motivasi Berprestasi - Ni Ketut Chitra Wati; Nyoman Dantes; Kadek Suranata (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
This study aims to present the results of research on the Effectiveness of the Behavioral Counseling Approach of Self Management Techniques for Reducing Academic Procrastination with Achievement Motivation Covariables in Grade VIII Students of Middle School. This research method uses the Experiment method. Respondents in this study amounted to 221 students of class VIII SMPN 1 Tabanan. This study used a pretest-posttest control group design and the sample was taken using a purposive random sampling technique. The data that has been collected was analyzed using one-way Anacova with the SPSS 17.0 application for Windows. The results of data analysis showed that the Behavioral Counseling Approach Self Management Techniques had an effective effect on reducing student academic procrastination after controlling the Variables of Achievement Motivation. This article suggests that teachers can use the Behavioral Counseling Approach to Self Management Techniques to Reduce Student Academic Procrastination. This article suggests that teachers pay more attention to the behavior of students who have tendencies or characteristics of academic procrastination in the application of learning to reduce student academic procrastination in implementing student learning activities to increase their learning motivation.